Oxidative carbonylation of aromatic amines by selenium compounds - Kim, HS; Kim, YJ; Lee, H; Lee, SD; Chin, CS (ACADEMIC PRESS INC, 1999)
Various factors affecting the oxidative carbonylation of aromatic amines were investigated in the presence of a catalyst system comprising SeO2 and alkali metal carbonate. An active catalyst, K2SeO3 was obtained from the reaction of SeO2 and K2CO3 in methanol and the activity was tested. The effects of added alkali metal salts, solvents, aromatic amine substrates, molar ratio of aniline to catalyst, temperature, and pressure on the catalytic activity were studied. The activation energy of the carbonylation of aniline was evaluated as 17.0 kcal/mol. The highest turnover frequency was found to be 2082/h at aniline/catalyst = 12,800. A plausible mechanism for the carbonylation of aniline to diphenyl urea and phenyl carbamate has also been proposed. (C) 1999 Academic Press.
Keywords: CARBAMATE ESTERS; ANILINE; CONVERSION; PHOSPHATE; PALLADIUM; CATALYST